Determination of Giardia duodenalis assemblages and multi-locus genotypes in patients with sporadic giardiasis from England. Issue 1 (December 2015) - Minetti, Corrado; Lamden, Kenneth; Durband, Caroline; Cheesbrough, John; Fox, Andrew; Wastling, Jonathan
Abstract Background The protozoanGiardia duodenalis is a common but highly diverse human parasite that comprises a complex of seven morphologically identical genetic assemblages, further divided into sub-assemblages. There is very little information available on the diversity ofGiardia sub-assemblages and multi-locus genotypes infecting people in the United Kingdom. In this study we studied the molecular epidemiology ofGiardia in symptomatic patients from North West England. Methods Whole faecal DNA was extracted from the faecal samples of 406Giardia cases and the parasites assemblage, sub-assemblage and multi-locus genotype were determined using PCR amplification, DNA sequencing and phylogenetic analysis of the beta-giardin, glutamate dehydrogenase, triose-phosphate isomerase and small-subunit ribosomal RNA genes. Information about age, gender and self-reported clinical outcomes was also collected from the patients to check for differences associated with the infectingGiardia assemblage. Results Our results showed a difference in the age prevalence of the two assemblages, with assemblage A being more common in older cases. Cases infected with assemblage B more often reported vomiting and a longer illness than cases infected with assemblage A. The majority of infections (64 %) were caused by assemblage B followed by assemblage A (33 %), while mixed-assemblage infections were rare (3 %). Assemblage A isolates mostly belonged to the sub-assemblage AII and showed completed identity with previously described isolates. The level of genetic sub-structuring was significantly higher in assemblage B isolates, since a higher proportion of novel assemblage B sequences was detected compared to assemblage A. A high number of assemblage B sequences showed heterogeneous nucleotide positions that prevented the unambiguous assignment to a specific sub-assemblage. Both previously described and novel multi-locus genotypes were described in both assemblages, and up to 17 different assemblage B multi-locus genotypes were found. Conclusions We have produced the first data on the parasite multi-locus genotypes in the UK and have demonstrated that the molecular diversity ofGiardia is similar to other developed countries. Furthermore, we showed that the parasite assemblages infecting humans may be associated with patients of different ages and with different clinical outcomes.